Paradigma Kedaulatan Pangan Sebagai Landasan Penanggulangan Krisis Pangan Global Dalam Perspektif Negara Hukum Kesejahteraan - Hotma P. Sibuea; Indra Lorenly Nainggolan; Jantarda Mauli Hutagalung (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
The Indonesian Constitution stipulates in Article 28H paragraph (1) as follows: “everyone has the right to live in physical and spiritual prosperity, to live and to have a good and healthy environment, and to have the right to health services”. The principle of a prosperous life as the right of every person is further regulated in Article 9 paragraph (2) of Law Number 39 of 1999 which stipulates as follows ” everyone has the right to live in peaceful, safe, peace, happy, physical and spiritual prosperity. One aspect of supporting a prosperous life is food. Food is one of the basic human needs that must be met in order to live a prosperous life. The Indonesian state and nation really understand the urgency of food in human life so that they can live in prosperity. Based on the idea of the urgency of food in a prosperous human life, Indonesia stipulates Law No. 18 of 2002 on Food. The Indonesian state is determined to achieve the ideals of